Combining dental and skeletal evidence in age classification: Pilot study in a sample of Italian sub-adults. (May 2016) - Pinchi, Vilma; De Luca, Federica; Focardi, Martina; Pradella, Francesco; Vitale, Giulia; Ricciardi, Federico; Norelli, Gian-Aristide
Highlights: Comparison of dental and skeletal age in the same sample of children. Combination of dental and skeletal ages through Linear Discriminant Analysis. Combination of dental and skeletal ages reduces false positives rates. Abstract: Background: Dental and skeletal maturation have proved to be reliable evidence for estimating age of children and prior studies and internationally accredited guidelines recommend to evaluate both evidence in the same subject to reduce error in age prediction. Nevertheless the ethical and legal justification of procedures that imply a double exposition of children stands as a relevant issue. This study aims to evaluate the accuracy of age estimation provided by a combination of skeletal and dental methods applied in the same sample of children. Materials and methods: The sample consisted of 274 orthopantomographies and left hand-wrist X-rays of Italian children, (aged between 6 and 17 years) taken on the same day. Greulich and Pyle's (GP), Tanner-Whitehouse's version 3 (TW3) and Willems' (W) and the Demirjian's (D) methods were respectively applied for estimating skeletal and dental age. A combination of skeletal and dental age estimates through Linear Discriminant Analysis (LDA) is proposed to obtain a classifier respect to an age threshold. Results: The combination of D and TW3 obtained an improvement of accuracy in classifying female subjects respect to the 12 years threshold respect to the original methods (from about 77% using either original methods to 83.3% combining TW3 + D) as well as a consistent reduction of false positives rate (from 17% to 21% for original methods to 5.6% with TW3 + D). For males the LDA classifier (based on TW3 and W) enable a small improvement in accuracy, whilst the decreasing of false positives was as noticeable as for females (from 17.6 to 14.1% for original methods to 6.2% combining TW3 + W). Conclusions: Although the study is influenced by the limited size and the uneven age distribution of the sample, the present findings support the conclusion that age assessment procedures based on both dental and skeletal age estimation can improve the accuracy and reduce the occurrence of false positives.